Local intensity estimation of solar radiation with vision‐based 3D modeling of local areas through unmanned aerial vehicle. Issue 1 (5th August 2021) - Kim, Sungkyum; Jang, Seungsoo; Choi, Chanho; Shin, Sung Gyun; Lee, Minjae; Cho, Woosung; Lee, Janghee; Han, Sangsoo; Kim, Jooyeon; Kim, Song Hyun
Abstract: The analysis of optimal locations for photovoltaic systems within urban regions has been raised as an important issue for increasing the relative efficiency of solar power generation in urban landscapes. This paper suggests a method that includes 3D modeling through unmanned aerial vehicle (UAV) flight strategies, shadow generation, solar radiation estimation, and evaluation of optimal areas to estimate cost‐effective candidate locations for installing solar panels. For testing the proposed method, combining generated shadows with the intensities of solar radiation in Pohang, South Korea, which were from data collected for a year, the average intensities were calculated to estimate regions for installing solar panels in the targeted places. It is expected that the strategy proposed in this study can contribute to the popularization on local intensity estimations of the solar radiation in urban landscape with using conventional UAV, which has high accessibility as well as realizing low estimation cost.